Cassava production and processing in Cote dIvoire: COSCA working paper, No. 23 - Nweke, F.; Ngoram, K.; Dixon, A.; Ugwu, B.; Ajobo, O. (2000)
Cassava was planted widely for sale; although tree crop production was the main source of cash income in the cassava-producing area, among food crops, cassava production was a source of cash income for the largest number of households. Cassava was the most important crop in the area studied, both in land area and farmers' ranking of the crops. Rice was second to cassava; maize, plantain, and yam were also important. Cassava land area expansion was reported in most villages in response to an increasing population of immigrants who worked in cocoa and coffee plantations. The villages which did not report the increasing trend were mainly around market centers where people had access to imported food and in areas where attieke, a convenient cassava food product, was made by manual methods which were very labor-intensive. The food crop production practices were heavily influenced by tree crop growing. About 80% of the representative villages intercropped food crops with cocoa or coffee in one or more of their rotation systems; all food crops were involved in this practice. While tree/food crop systems were entirely continuous cultivation of food crops, food crop systems were 20% continuous cultivation with crop rotation and 80% fallow rotation. Fallow rotation was dominant because population densities were low and climate was mostly humid. There was turnover in cassava cultivars grown by farmers, who continually introduced new cassava cultivars with desired attributes into their cropping systems. Such cultivars were not necessarily improved varieties but were often local and varied with villages and regions. As they introduced new cultivars, farmers often abandoned existing cultivars that might not possess desired attributes. The farmers were selecting the cultivars for high root yield, low cyanogen level, large canopy for weed control, and good processing qualities. Although population pressure on land was low in the country in comparison with the other countries in the COSCA study, cassava root yield was below average. The cassava stand density which influenced the root yield positively and significantly was also below the average for other countries. Intensified land-use practices which also influenced the root yield positively and significantly were not adopted because population pressure on land was low. Purchased inputs including high yielding varieties were not adopted even though access to market conditions was better than average because the availability of imported rice around the market centers discouraged private investment in the use of the purchased inputs. In addition, most of the survey sites were in the humid zone where the root yield was low relative to the sub-humid zone in other countries; and most of the cassava fields were planted with sweet cassava cultivars which were harvested early \with low yields. The local cultivars were susceptible to the major cassava plant pests/diseases. The majority of cassava producers relied mainly on crop rotation, fallow management, and cultivar selection from among the available landraces to control the problems. Cassava was commonly processed although more than 90% of the production was of the sweet cassava types. Processing labor-saving technology was available, but was not widely adopted. Similarly, the technique for making a convenient cassava food product was known but the product market centers. Imported rice had an adverse influence on the demand for this product. The consequence was that the availability of the improved processing technologies did not produce the same result as in neighboring West African countries, Nigeria and Ghana, namely, an increasing trend in cassava land area.